2012
DOI: 10.1071/fp11229
|View full text |Cite
|
Sign up to set email alerts
|

Ecotypic responses of switchgrass to altered precipitation

Abstract: Anthropogenic climate change is projected to alter precipitation patterns, resulting in novel environments for plants. The responses of dominant plant species (e.g. Panicum virgatum L. (switchgrass)) to climate changes can drive broader ecosystem processes such as primary productivity. Using a rainfall mesocosm facility, three ecotypes of P. virgatum (collected from Kansas, Oklahoma and Texas, USA) were subjected to three precipitation regimes (average, -25%, +25%) to determine the physiological and growth res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 65 publications
(76 reference statements)
1
32
0
Order By: Relevance
“…Classic physiological studies addressed differences in leaf performance between ecologically differentiated upland and lowland switchgrass populations with distinct vegetative phenotypes and ploidy levels [32,34]. Evidence for local adaptation [35,36] has also led to more recent experiments focused on inter-population variation in productivity and physiological performance [6,33,[37][38][39][40]. Results from these experiments support differences in seasonal patterns of photosynthetic performance that complement adaptive variation in phenology [33,39,40].…”
Section: Introductionmentioning
confidence: 65%
“…Classic physiological studies addressed differences in leaf performance between ecologically differentiated upland and lowland switchgrass populations with distinct vegetative phenotypes and ploidy levels [32,34]. Evidence for local adaptation [35,36] has also led to more recent experiments focused on inter-population variation in productivity and physiological performance [6,33,[37][38][39][40]. Results from these experiments support differences in seasonal patterns of photosynthetic performance that complement adaptive variation in phenology [33,39,40].…”
Section: Introductionmentioning
confidence: 65%
“…In comparison, Hartman et al (2012) found no differences in A CO2 per unit transpiration among three latitudinally separated P. virgatum populations, yet significantly higher photochemical efficiency in southern populations.…”
Section: Researchmentioning
confidence: 91%
“…In contrast, switchgrass has been reported to be impacted by changes in water availability. Earlier reports [20,35] indicated that WUE declines with increased water availability in switchgrass. Stout et al [21] indicated soil attributes, such as water holding capacity, make the largest contribution to WUE in switchgrass under variable precipitation scenarios.…”
Section: Water Use Efficiencymentioning
confidence: 99%
“…However, other factors besides photosynthetic pathway affect WUE. Switchgrass biomass production is strongly driven by precipitation, but as precipitation increases, WUE decreases [20]. Precipitation variability can impact switchgrass WUE and yields [21].…”
Section: Introductionmentioning
confidence: 99%